Late Burdigalian sea retreat from the North Alpine Foreland Basin: new magnetostratigraphic age constraints - Sant, K.; Kirscher, Uwe; Reichenbacher, B.; Pippèrr, M.; Jung, D.; Doppler, G.; Krijgsman, W. (Elsevier Science BV, 2017)
© 2017 Elsevier B.V.Accurate reconstruction of the final sea retreat from the North Alpine Foreland Basin (NAFB) during the Burdigalian (Early Miocene) is hampered by a lack of reliable age constraints. In this high resolution magnetostratigraphic study we try to solve a significant age bias for the onset of the Upper Freshwater Molasse (OSM) deposition in the neighboring S-German and Swiss Molasse Basins. We measured > 550 samples from eleven drill cores covering the transition from marine to brackish to freshwater environments in the S-German Molasse Basin. Based on combined bio-, litho- and magnetostratigraphic constraints, the composite magnetostratigraphic pattern of these cores provides two reasonable age correlation options (model 1 and 2). In model 1, the base of the brackish succession lies within Chron C5Cr (~ 16.7–17.2 Ma), and the onset of OSM deposition has an age of ~ 16.5 Ma. Correlation model 2 suggests the transition to brackish conditions to be within C5Dr.1r (~ 17.7–17.5 Ma), and yields an age around 16.7 Ma for the shift to the OSM. Most importantly, both models confirm a much younger age for the OSM base in the study area than previously suggested. Our results demonstrate a possible coincidence of the last transgressive phase (Kirchberg Fm) with the Miocene Climatic Optimum (model 1), or with the onset of this global warming event (model 2). In contrast, the final retreat of the sea from the study area is apparently not controlled by climate change.